PENINGKATAN PENGETAHUAN DAN PELATIHAN PRODUKSI DODOL SEBAGAI DIVERSIFIKASI LABU KUNING (CUCURBITA MOSCHATA) PADA MASYARAKAT DESA MENDALE ACEH TENGAH - Kamarudin, Anna Permatasari; Asry, Lenawati; Ratnawati, Ratnawati; Khairani, Elisa; Purnama, Rizskywan; Asri, Rahmadi; Amna, Amna; Sabri, Sabri; Hidayat, Anwar; Agustina , Via; Rejeki, Seri (LPPM STAI Muhammadiyah Probolinggo, 2025)
Mendale Village is one of the villages in Takengon, Central Aceh, located on the shores of Lake Laut Tawar. So far, Mendale Village has not had a product that can be used as a typical souvenir from Mendale Village and can increase community income. In fact, Mendale Village has a lot of natural resources. The existence of resources in the form of yeloow pumpkin can be processed into dodol. Therefore, the purpose of this Community Service program is to increase the knowledge and skills o the Mendale Village community to process tallow pumpkin into yellow pumpkin dodol which can be used as a typical culinary souvenir. The commnutiy service method used is through counceling and demonstration. The partners who attended came from mothers from the general public and the Family Welfare Empowerment Movement Team, totaling 20 people. The results of the Pre Test and Post Test that communit knowledge and skills had increased. Especially regarding the use of yellow pumpkin in food and beverage products, including dodol products and the existence of these products, including dodol products and the exixtence of theses products will provide added value to yellow pumpkin. The results of the implementation evaluation showed that almost all partners stated ‘Strongly Agree’ to several statements. The statements are, regarding the event schedule, the training material is appropriate, the theme is interesting, the program is very usefull and partners will follow the same program if it is held again in the future, each statement gets a percentage of 100% or all partners, 20 people stated ‘Strongly Agree’.